Factors affecting the distribution and prevalence of oral mucosal lesions in complete denture wearers - TÜRKER, ŞEBNEM BEGÜM (WILEY, 2011)
Objective: To determine the frequency of the oral lesions related to gender, age, the length of time of denture usage, education level and economic status. Methods: The 153 patients with old complete dentures (CD) were asked to participate in the investigation. The subjects (76 male and 77 female) were 37-85 years of age with a mean age of 61.8 +/- 9.8 years. Education, economic status and age factors were estimated in subgroups. The data obtained were evaluated by one-way anova, Mann-Whitney U-test, Kruskal-Wallis test, Student's t-test and chi-squared test. The level of statistical significance was set at p < 0.05. Results: The patients who had denture stomatitis and traumatic ulcers were statistically significantly older than the ones who did not have these lesions (p < 0.05). Based on the length of denture usage, patients who had a flabby ridge, fibrous inflammatory hyperplasia, traumatic ulcers (p < 0.01) and denture stomatitis (p < 0.05) were using their dentures statistically significantly longer than the ones who had healthy tissues. Conclusions: The CD wearers should be advised to visit their dentist regularly to prevent oral mucosal lesions due to the changing supporting tissues during the length of denture usage and to improve their quality of life.
Keywords: complete denture; length of denture usage; oral mucosal lesion; FIBROUS INFLAMMATORY HYPERPLASIA; POPULATION; MANAGEMENT; HEALTH; STOMATITIS; DENTISTRY; ETIOLOGY; CHINESE; HABITS; SCHOOL